Social determinants of hypertension and diabetes among African immigrants: the African immigrants health study. Issue 6 (18th August 2022) - Ogungbe, Oluwabunmi; Turkson-Ocran, Ruth-Alma; Nkimbeng, Manka; Cudjoe, Joycelyn; Miller, Hailey N.; Baptiste, Diana; Himmelfarb, Cheryl Dennison; Davidson, Patricia; Cooper, Lisa A.; Commodore-Mensah, Yvonne
ABSTRACT: Objective: To examine the association between social determinants of health, hypertension, and diabetes among African immigrants. Methods: The African Immigrant Health Study was a cross-sectional study of the health of African immigrants in the Baltimore-Washington Metropolitan Area. The outcomes of interest were self-reported diagnoses of hypertension and diabetes. Logistic regression was used to examine the relationship between educational status, employment, income, social support, health insurance, and self-reported diagnoses of hypertension and diabetes, adjusting for age, sex, and length of stay in the U.S. Results: A total of 465 participants with mean (±SD) age 47 (±11.5) years were included. Sixty percent were women, 64% had a college degree or higher, 83% were employed, 67% had health insurance, and 70% were married/cohabitating. Over half (60%) of the participants had lived in the United States for ≥ 10 years, and 84% were overweight/obese. The overall prevalence of hypertension and diabetes was 32% and 13%, respectively. The odds of diabetes was higher (aOR: 5.00, 95% CI: 2.13, 11.11) among those who were unemployed than among those who were employed, and the odds of hypertension was higher among those who had health insurance (aOR:1.73, 95% CI: 1.00, 3.00) than among those who did not. Conclusions: Among African immigrants, those who were unemployed had a higher likelihood of a self-reported diagnosis of diabetes than those who were employed. Also, people who had health insurance were more likely to self-report a diagnosis of hypertension. Additional studies are needed to further understand the influence of social determinants of health on hypertension and diabetes to develop health policies and interventions to improve the cardiovascular health of African immigrants.